2013
DOI: 10.5505/tjtes.2013.99389
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Analysis Of 132 Patients With Orbital Fracture

Abstract: BACKGROUND:The aim of this study was to evaluate the clinical and epidemiological features of 132 patients with orbital wall fracture who were treated at Şişli Etfal Teaching and Research Hospital, Istanbul, between 2005-2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
3
5
0
Order By: Relevance
“…Road traffic accidents are the most frequent cause of orbital walls fractures in urban areas, according to Cruz and Eichenberger’s review ( 15 ). The most common cause of all orbital walls fractures in the current study was RTA, followed by violence only in male patients, which is consistent with the study that found the etiology of orbital walls fractures to be RTA, assaults, and falls, in decreasing order of frequency ( 16 ). Contrarily, Shere et al .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Road traffic accidents are the most frequent cause of orbital walls fractures in urban areas, according to Cruz and Eichenberger’s review ( 15 ). The most common cause of all orbital walls fractures in the current study was RTA, followed by violence only in male patients, which is consistent with the study that found the etiology of orbital walls fractures to be RTA, assaults, and falls, in decreasing order of frequency ( 16 ). Contrarily, Shere et al .…”
Section: Discussionsupporting
confidence: 92%
“…This current study confirmed previous research that the inferior wall is the most affected orbital wall fracture and that the inferior wall is also the most frequently afflicted orbital regions ( 19 ). Contrary to the literature, it was discovered that medial wall fractures were more common ( 16 ). This discrepancy might be caused by the fact that medial wall fractures are underdiagnosed because they do not have any symptoms ( 23 ).…”
Section: Discussionmentioning
confidence: 84%
“…1 Cagatay et al in their study also found that the common walls affected were the floor and the lateral wall. 11 The increased incidence of lateral wall fractures in our study is due to the high number of road traffic accidents.…”
Section: Pattern Of Orbital Fracturesmentioning
confidence: 63%
“…Our study revealed the most common age group to be affected as 16-35 years old (58.33%) Most authors agree that by far the most commonly affected age group is the 20-40 years. In a retrospective analysis of 132 patients with orbital fracture 19 , the most affected age group was the 31-40-year-old age range (24.2%), followed by the age groups of 21-30 years (22%) and 11-20 years (22%). The age group also is in agreement with the findings of other authors such as Silva et al 20 .…”
Section: Discussionmentioning
confidence: 99%